2014
DOI: 10.1152/ajpregu.00049.2014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and altered lipid homeostasis in the programming of offspring fatty liver by maternal obesity

Abstract: Changes in the maternal nutritional environment during fetal development can influence offspring's metabolic risk in later life. Animal models have demonstrated that offspring of diet-induced obese dams develop metabolic complications, including nonalcoholic fatty liver disease. In this study we investigated the mechanisms in young offspring that lead to the development of nonalcoholic fatty liver disease (NAFLD). Female offspring of C57BL/6J dams fed either a control or obesogenic diet were studied at 8 wk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
105
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 42 publications
3
105
0
2
Order By: Relevance
“…77 Human studies using magnetic resonance imaging have shown that maternal BMI predicts infant intrahepatocellular lipid storage, as seen in animal models, which implies that maternal obesity may predispose the offspring to developing nonalcoholic fatty liver, the hepatic manifestation of metabolic syndrome. 78,79 Furthermore, maternal obesity appears to downregulate fetal myogenesis. Skeletal muscle is the principal site for glucose and fatty acid utilization.…”
mentioning
confidence: 99%
“…77 Human studies using magnetic resonance imaging have shown that maternal BMI predicts infant intrahepatocellular lipid storage, as seen in animal models, which implies that maternal obesity may predispose the offspring to developing nonalcoholic fatty liver, the hepatic manifestation of metabolic syndrome. 78,79 Furthermore, maternal obesity appears to downregulate fetal myogenesis. Skeletal muscle is the principal site for glucose and fatty acid utilization.…”
mentioning
confidence: 99%
“…Changes in gene methylation have been identified to be important in the context of upregulation of genes that control hepatic fatty acid oxidation and gluconeogenesis in energydemanding tissues (i.e., liver, heart muscle; Tables 1 and 3). Whereas recent studies in rodent models of maternal overnutrition identified a sex-specific upregulation of hepatic expression of Pparg (Table 3) (2,24), nutritional effects in animal models of poor nutrition were shown to be mediated through Ppara and the glucocorticoid receptor (Nr3c1, also known as Gr; Table 1 and Fig. 1) (17,87,89,129).…”
Section: Maternal Nutrition As a Modifier Of Epigenetic Regulation Ofmentioning
confidence: 97%
“…A growing body of evidence has associated maternal nutrition with altered offspring metabolism (Alfaradhi et al, 2014;Ornellas et al, 2015). A high fat (HF) fed mothers favors the early onset of obesity and its comorbidities in the offspring even when there is balanced nutrition in their postweaning life (Gregorio et al, 2010).…”
Section: Introductionmentioning
confidence: 99%